On the equicontinuity of one family of inverse mappings in terms of prime ends - Salimov, R. R.; Sevost'yanov, E. A. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
For a class of mappings satisfying upper modular estimates with respect to families of curves, we study the behavior of the corresponding inverse mappings. In the terms of prime ends, we prove that the families of these homeomorphisms are equicontinuous (normal) in the closure of a given domain.